Behavioral Neurobiology of Anxiety and Its Treatment - Stein, Murray B.; Steckler, Thomas; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2010)
The book aims to cover a broad range of topics related to anxiety disorders, including symptomatology, etiology, epidemiology, diagnostic features, comorbidity, clinical neuroscience, genetics, neuroanatomy, neuroendocrinology, neurochemistry, animal models, translational science, functional neuroimaging, and preclinical and clinical psychopharmacology. The book aims at bringing these disciplines together to provide an update of the field and outlook to the future. Therefore, it will be of use to both the non-clinical and clinical expert, who may use it as a detailed reference book, and the novist to the field, to whom it may serve as an introductory text, providing an overview.
Anxiety Disorders Diagnosis: Some History and Controversies -- Epidemiology of Anxiety Disorders -- Comorbidity in Anxiety Disorders -- Genetics -- Neuroanatomy of Anxiety -- Stress and the Neuroendocrinology of Anxiety Disorders -- Animal Models of Anxiety and Anxiolytic Drug Action -- Genetic Approaches to Modeling Anxiety in Animals -- Behavioral Correlates of Anxiety -- Challenging Anxiety: A Focus on the Specificity of Respiratory Symptoms -- Functional Neuroanatomy of Anxiety: A Neural Circuit Perspective -- Pharmacological Enhancement of Behavioral Therapy: Focus on Posttraumatic Stress Disorder -- The Pharmacology of Anxiety -- GABAA Receptor ?2/?3 Subtype-Selective Modulators as Potential Nonsedating Anxiolytics -- Antidepressant Treatment in Anxiety Disorders -- Metabotropic Glutamate Receptors: Their Therapeutic Potential in Anxiety -- Developing Small Molecule Nonpeptidergic Drugs for the Treatment of Anxiety Disorders: Is the Challenge Still Ahead? -- Cannabinoids and Anxiety -- Pharmacological Treatment of Generalized Anxiety Disorder -- Pharmacologic Treatment of Panic Disorder -- Pharmacotherapy of Social Anxiety Disorder -- Pharmacotherapy of Post-Traumatic Stress Disorder -- Pharmacological Treatment of Obsessive-Compulsive Disorder.
Keywords: Medicine; Neurosciences; Toxicology; Psychiatry; Biomedicine; Neurosciences; Psychiatry; Pharmacology/Toxicology.